The Design, Development, and Validation of a Residual Limb Evaluation System for the Real-Time Data Mapping of the Trans-Tibial Amputee Socket-Limb Interface for Prosthetic Fitment - Bruton, Scott (Division of Biomedical Engineering, 2022)
Introduction: Skin problems are known to occur on the residual limb (RL) of trans-tibial amputees (TTAs). These are induced by an improper prosthetic socket fitment, alignment or component selection. It was identified that there is a lack of RL evaluation systems (RLESs) that are tailored for the prosthetic fitting procedure that analyse the pressures and temperatures on the RL, as well as the gait phases of stance. This observation established the hypothesis that a tactile RL evaluation device and recording software system can provide reliable socket-limb interface (SLI) information which can be used to identify vulnerable areas on the RL induced by the socket during the gait movements of TTAs. Methods: A prototype RLES was designed and developed. It was comprised of tactile pressure and temperature transducers, gait ground reaction force (GRF) transducers and device-specific software tailored for the evaluation of the RL within the SLI. A pilot study was designed to evaluate the capabilities of the RLES which entailed the evaluation of its skin temperature tracking ability, pressure measurement repeatability within the SLI, and ability to interpret the pressures during (natural) walking movements. Study participants were recruited through the private practice of prosthetist Eugene Russouw, as well as Vincent Palloti Hospital (South Africa, Cape Town) and consisted of two bilateral and three unilateral TTAs, who were enrolled in the pilot study. Each participant performed three experimental procedures: a static stand (SS); a straight-line walk (SLW); and a figure-of-8 walk (F8W). Skin temperature change due to loading and unloading was monitored during the SS procedure. Peak pressure results from the SLW and F8W procedures were gathered to evaluate the coefficient of variance (COV) between strides. This was used to evaluate the repeatability of the pressure measurements and allowed for a comparison between the SLW and F8W methods. GRF data collected from the SLW dataset was used to evaluate the RLES's ability to track gait phases. Results: The developed RLES software provided a tailored prosthetic fitting analysis platform (in the form of a graphical user interface) which allowed the user to perform a real-time, in-depth analysis of different RL areas, as well as provided an overview of all areas simultaneously. It provided functions for the recording, playback, and export of testing data which was used to evaluate the RLES capabilities. The RLES produced an average COV of 7.16%, which fell within the 6.94% ± 1.7% range in literature. The SS procedure produced an average temperature increase of 0.45 °C, found over all RL areas, which corresponds to similar studies in literature. This validated its ability to track RL skin temperature by producing the expected skin temperature change trend. Additionally, the RLES produced an expected TTA gait GRF curve (similar to literature) in which different gait phases could be identified. The comparison between the SLW and F8W methods found that pressure sore areas endured large pressures without relief from other movements (when compared to healthier areas), and suggests that the SLW and F8W comparison may be an important additional evaluation method during the prosthetic fitting procedure. The RLES identified all of the pressure sores presented within the 24 RL areas over all the TTA participants and suggested that a safe pressure threshold of 100 kPa is an appropriate guideline to be used during the prosthetic fitting procedure. Conclusions: The RLES proved to work efficiently and successfully within the study, and was capable of identifying vulnerable areas of pressure sores. With the high prevalence of skin problems on the RLs of TTAs, the implementation of a RLES during the fitting procedure, which can tailor the prosthesis design and fitment to the amputee, may potentially identify vulnerable areas of future skin problems and allow preventative actions to be performed.